Trend 1998 - 2003. Statistics Canada. CANSIM: Manufacturing - General | Country: Canada | Province: Northwest Territories | Table: Annual survey of manufactures (ASM), sales of manufactured goods by North American Industry Classification System (NAICS) and industry sub-sector | Variable: Manufacturing, Incorporated businesses with employees having sales of manufactured goods greater than or equal to $30,000 | Units: $CAD x 1,000, 1998-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-149. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Manufacturing - General | Country: Canada | Province: Northwest Territories | Table: Annual survey of manufactures (ASM), sales of manufactured goods by North American Industry Classification System (NAICS) and industry sub-sector | Variable: Manufacturing, Incorporated businesses with employees having sales of manufactured goods greater than or equal to $30,000 | Units: $CAD x 1,000, 1998-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-149. Dataset: Presents statistics on general topics related to the manufacturing industry in Canada. Topics cover many subtopics, or are too specific to correspond to any of the subtopics. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Manufactured Goods, Manufacturing Businesses, Manufacturing Industry